2017
DOI: 10.18794/aams/63507
|View full text |Cite
|
Sign up to set email alerts
|

Importance of zinc for the human body in the aspect of zinc supplementation

Abstract: ST R ES ZCZ E NI ECynk jest jednym z głównych pierwiastków śladowych organizmu, spełniającym rolę katalityczną, strukturalną i regulacyjną. Jest niezbędny do podziałów komórkowych i różnicowania powstających komórek, uczestniczy w homeostazie, reakcjach odpornościowych, w apoptozie i starzeniu się organizmu. Cynk jest również składnikiem wielu enzymów i białek oraz odgrywa ważną rolę w spermatogenezie i syntezie hormonów steroidowych. Niedostateczna podaż cynku dotyczy ok. 30% ludności świata. Oprócz niedostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Dietary zinc deficiency affects approximately 30% of the world population [ 61 ]. In the authors’ own study of the diet of the Polish population conducted in 2000-2003, including the assessment of the zinc content, two methods of data collection were applied simultaneously: a questionnaire for the assessment of the whole-day diet from 24 hours preceding the day of data collection with the use of an interview questionnaire, and the use of household budget surveys by the Central Statistical Office.…”
Section: Zinc Selenium and Vitamin Dmentioning
confidence: 99%
“…Dietary zinc deficiency affects approximately 30% of the world population [ 61 ]. In the authors’ own study of the diet of the Polish population conducted in 2000-2003, including the assessment of the zinc content, two methods of data collection were applied simultaneously: a questionnaire for the assessment of the whole-day diet from 24 hours preceding the day of data collection with the use of an interview questionnaire, and the use of household budget surveys by the Central Statistical Office.…”
Section: Zinc Selenium and Vitamin Dmentioning
confidence: 99%
“…In 1934 and 1961 it was shown that this element is also necessary for the proper development of animals and humans [ 5 ]. Zinc is involved in the action of over 300 enzymes that catalyze hydrolysis reactions or the transport of functional groups [ 6 , 7 ]. The daily requirement for zinc, depending on age, ranges from 2 mg for infants to 11–13 mg for adults, including pregnant and breastfeeding women [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, it should be remembered that an excess of zinc and other microelements may be harmful, according to the Paracelsus principle—everything is a poison and nothing is a poison, it is the dose that makes the poison. For example, employees working in zinc smelters are exposed to excessive doses of zinc, where they suffer from an occupational disease called foundry fever [ 6 , 11 , 12 ]. Based on these few examples, it can be seen that controlling the level of zinc as well as a whole range of macro- and microelements is necessary for the proper functioning of living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…ZnT proteins reduce the concentration of zinc in the cytoplasm, either transporting zinc outside the cell or moving it to extracellular fluids, while ZIP proteins have the opposite effect—they allow the influx of zinc from the vessels into the cell. Zinc may be transported from the intestinal lumen into the enterocytes via a non-specific divalent metal transporter (DMT1) [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%